Peran Paklobutrazol dan Pupuk dalam Mengendalikan Tinggi Tanaman dan Kualitas Bunga Krisan Pot - Rochmatino Rochmatino; Iman Budi Santoso; Murni Dwiati (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
The objective of this study was to determine the effect of paklopbutrazol concentration and fertilizer on plant height and flower quality of potted chrysanthemum. The experimental method was used with factorial design. The first factor was paklobutrazol with the concentration as follow: 0, 100, 200, and 300 ppm. The second factors were cow, chicken, and goat manure. Parameters observed were plant height, time of flowers emerging, flower diameter and freshness. The results showed that certain concentration of paklobutrazol might inhibited plant height, time of flowers emerging, and shortening of flowers freshness, while chicken manure fertilizer spurred flower diameter.